Perilaku Ekonomi Bank Syariah dan Risikonya Terhadap Rate of Return Bagi Nasabah Deposan Dalam Pembiayaan Mudarabah dan Murabahah (Studi Kasus Bank-bank Syariah di Wilayah Yogyakarta) - Abdul Mughits (Aplikasia: Jurnal Aplikasi Ilmu-ilmu Agama, 2016)
This research tries to check the potency of risk of Islamic bank in defrayal of mudarabah and murabahah. This research was inspired from ascription of whereas one who said that the Islamic banks have not been risk because they have owned the guidance of risk management published by Bank Indonesia (BI). One way to assess the existence of potency of risk of Islamic bank in its defrayal product is using the theory of behavioral economics which’s in general differentiated to two categories, that is rational that which tends to be risk and irrasional that which tend to be not risk. Rational behavior is presented by the approach of efficiency market hyphotesis (EMH) and irrational behavior is presented by the approach of adaptive market hypothesis (AMH) And behavioral finance (BF). This research objects are four Islamic banks in Yogyakarta. After conducting by tracing of field data then found by that four Islamic banks affirm still face the risk in their operational, especially operational risk, risk of credit and risk of liquidity. From four bank also show that their behaviors are irrasional because tend to show the behavior of AMH and BF, than EMH. Thereby its risk potency tend to minimize to rate of return of client of deposan or third party lenders ( DPK).